1987
DOI: 10.1126/science.2823385
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role of Silent Receptors of Atrial Natriuretic Factor

Abstract: A ring-deleted analog of atrial natriuretic factor--des[Gln18, Ser19, Gly20, Leu21, Gly22] ANF4-23-NH2 (C-ANF4-23)--binds with high affinity to approximately 99% of ANF receptors in the isolated perfused rat kidney. In this preparation, C-ANF4-23 is devoid of detectable renal effects and does not antagonize any of the known renal hemodynamic and natriuretic actions of biologically active ANF1-28. In contrast, both C-ANF4-23 and ANF1-28 increase sodium excretion and decrease blood pressure in intact anesthetize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
397
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 913 publications
(405 citation statements)
references
References 23 publications
5
397
0
2
Order By: Relevance
“…However, the possible mechanisms for the cardioprotective effects of the three natriuretic peptides on I/R seem to be controversial. NPRC activation is thought to be responsible for the cardioprotective role of CNP as mentioned above, and the selective agonist of NPRC (cANF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ) also reduces infarct size and maintains coronary perfusion pressure [12]. Studies of ANP and BNP effects show the involvement of cGMP generated via the NPRA receptor in the reduction of infarct size [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the possible mechanisms for the cardioprotective effects of the three natriuretic peptides on I/R seem to be controversial. NPRC activation is thought to be responsible for the cardioprotective role of CNP as mentioned above, and the selective agonist of NPRC (cANF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ) also reduces infarct size and maintains coronary perfusion pressure [12]. Studies of ANP and BNP effects show the involvement of cGMP generated via the NPRA receptor in the reduction of infarct size [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…ANP and BNP are ligands of NPRA, while CNP preferentially binds to NPRB. NPRC has similar affinity to all three natriuretic peptides and is commonly considered a clearance receptor [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In theory, at least, such combined NEP\ACE inhibitors should provide benefits beyond ACE inhibition alone. An alternative approach, yet to be assessed in man, is to augment endogenous circulating levels of ANP and BNP through blockade of receptors that normally contribute to clearance of the peptides from plasma [8].…”
mentioning
confidence: 99%
“…Maack and his co-workers have reported that ANP-R2 is biologically silent and the most important role of this receptor is clearance of ANP acts as a hormonal buffer system to modulate its plasma levels, thus being called a clearance receptor [9]. However, Cantin and colleagues have recently reported that ANP-R2 is coupled to the adenylate cyclase/cAMP system through an inhibitory guanine-nucleotide-binding regulatory protein (Gi), leading to a decrease in the intracellular cAMP level [lo].…”
mentioning
confidence: 99%